ANALISIS POSITIONING TRUK KELAS 2 TON SEBAGAI DASAR PENENTUAN STRATEGI POSITIONING di Eks KARESIDENAN BESUKI: Manajemen pemasaran - ENDANG NARYONO, SE., MM (P3M STIE PASIM Sukabumi, 2018)
This Research aim to to analyse map of ATPM class truck positioning 2 ton pursuant to perception of consumer in Ex Besuki karesidenan. Elementary which used to position ATPM truck 2 ton is perception of consumer to determinant attribute looking like which compose product, price, salesman, discounted, availibility of spar-part, price sell again, access price, endurance, strength of machine, payload capacities, suspensi, each fuel efficiency and akselerasi of Truck class ATPM 2 ton. Technique analyse is Multidimensional Scaling ( MDS). This Research is done/conducted by taking responder counted 100 responder with method of purposive sampling. obtained data to be tested to use analysis of MDS to know and And Reliability Validity, result of map of ATPM class truck positioning 2 ton ( Mitsubishi Canter, Toyota Dyna, Hino Dutro and of Isuzu ELF)) pursuant to perception of consumer, and equality of responder attitude in giving assessment. Pursuant to result of analaisis there are difference of each position of Truck class ATPM 2 ton pursuant to perception of consumer and indicate that ATPM brand ton second class truck of Hino Dutro represent competitor closest or direct competitor (competitor direct) of brand of Toyota Dyna, especially concerning price, discounted, availibility of access, price sell again, access price, endurance, strength of machine, payload capacities, suspensi, fuel efficiency and akselerasi. Operator of Mitsubishi Canter and of Isuzu ELF don't have direct competitor because owning biggest difference or unique and clear diferensiasi. Pursuant to its Positioning of Mitsubishi represent vehicle owning nimble akselerasi and price sell high again and have weakness at payload capacities which small relative, Toyota represent strong vehicle and big energy